Application of AHP for Selection of Environmentally Friendly Crop Cultivation in Mae Hong Son Province - Kunasri, Kasem; Panmanee, Chanita (Journal of Applied Economics and Management Strategy, 2021)
ABSTRACT The purpose of this research was to analyze alternative plant models under environmentally friendly production systems through participatory processes of the communities in Mae Hong Son province. The 140 samples consisting of farmers and stakeholders were selected by using purposive sampling method. The analytical hierarchy process (AHP) was used as a tool for decision making. Under the criterions of physical characteristic, and sustainability aspect, there were nine feasible environmentally friendly crops that could be cultivated in the Mae Hong Son province which were separated into three crop types such as field crops, horticulture, and vegetable. The results shown that tiger peanut, garlic, and cabbage were the first priorities of each crop type. In addition, under the conditions of waste control, waste treatment, reduce, reuse and recycle, pollution prevention, and water conservation, tiger peanut should be planted in the Mueang and Pang Mapha districts, garlic should by grown in the Pai and Khun Yuam districts, and cabbage should be cultivated in the Sop Moei and Pang Mapha districts. The findings of this research were used for creating environmentally friendly alternative crop production manuals and policy recommendations for sustainable natural resource management in the Mae Hong Son province.